Recommendations for secure and sustainable European cultural landscapes.
Following its final conference that took place in Brussels on 4 October 2016, the EU-funded HERCULES consortium has provided stakeholders with a detailed set of policy recommendations that will preserve Europe's diverse heritage in cultural landscapes.